The MpsB protein contributes to both the toxicity and immune evasion capacity of Staphylococcus aureus. Issue 10 (7th October 2021) - Douglas, Edward J. A.; Duggan, Seána; Brignoli, Tarcisio; Massey, Ruth C.
Abstract : Understanding the role specific bacterial factors play in the development of severe disease in humans is critical if new approaches to tackle such infections are to be developed. In this study we focus on genes we have found to be associated with patient outcome following bacteraemia caused by the major human pathogen Staphylococcus aureus . By examining the contribution these genes make to the ability of the bacteria to survive exposure to the antibacterial factors found in serum, we identify three novel serum resistance-associated genes, mdeA, mpsB and yycH . Detailed analysis of an MpsB mutant supports its previous association with the slow growing small colony variant (SCV) phenotype of S. aureus, and we demonstrate that the effect this mutation has on membrane potential prevents the activation of the Agr quorum sensing system, and as a consequence the mutant bacteria do not produce cytolytic toxins. Given the importance of both toxin production and immune evasion for the ability of S. aureus to cause disease, we believe that these findings explain the role of the mpsB gene as a mortality-associated locus during human disease.